2012
DOI: 10.1212/wnl.0b013e31826e9a83
|View full text |Cite
|
Sign up to set email alerts
|

Serum tight-junction proteins predict hemorrhagic transformation in ischemic stroke patients

Abstract: Analyzing serum levels of TJ proteins, like CLDN5, OCLN, and CLDN5/ZO1 ratio, as well as S100B and VEGF, is an effective way to screen for clinical deterioration caused by HT in ischemic stroke patients, both within and after the IV thrombolysis time window.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(111 citation statements)
references
References 39 publications
3
98
0
Order By: Relevance
“…41 The role of TJPs in early HT is unclear since one study found intact TJPs at 24 hours after stroke 74 whereas a human study found increased blood levels of TJPs to be predictive of HT. 75 Early Hemorrhagic Transformation: Role of Other Leukocyte Factors Though leukocyte-derived MMPs appear to be one mediator of early HT, additional leukocyte-derived molecules have been implicated. 76 We examined mRNA expression in blood within 3 hours of ischemic stroke onset in humans before administration of tPA.…”
Section: Early and Delayed Hemorrhagic Transformationmentioning
confidence: 99%
“…41 The role of TJPs in early HT is unclear since one study found intact TJPs at 24 hours after stroke 74 whereas a human study found increased blood levels of TJPs to be predictive of HT. 75 Early Hemorrhagic Transformation: Role of Other Leukocyte Factors Though leukocyte-derived MMPs appear to be one mediator of early HT, additional leukocyte-derived molecules have been implicated. 76 We examined mRNA expression in blood within 3 hours of ischemic stroke onset in humans before administration of tPA.…”
Section: Early and Delayed Hemorrhagic Transformationmentioning
confidence: 99%
“…S-100 Protein: Measurement of serum S-100 protein levels in the first 10 days after stroke onset helps to predict long term clinical outcome and final infarct size [102]. The level of S-100 protein independently predicts HT before rtPA treatment, however with too low diagnostic accuracy to be useful in the preselection of patients for rtPA therapy [104,105].…”
Section: Blood Markers Nsementioning
confidence: 99%
“…MMP-9 and neutrophil levels are elevated in the cerebrospinal fluid as well. Since rtPA itself promotes neutrophil degranulation, a peak of MMP-9 elevation can be detected 30 minutes after rtPA administration as well [105][106][107].…”
Section: Mmp-9 Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of NSE in CSF reaches its peak on the third day after cerebral ischemia in rats, and is positively correlated with the final infarction volume [6]. The up-regulation of NSE level in serum lags behind that in brain tissue for 2 hours in permanent cerebral ischemia model [7,8]. Myelin basic protein (MBP) is an important myelin structural protein.…”
Section: Introductionmentioning
confidence: 99%